Efficient aimpoint tracking using target range profiles of a wideband FMCW seeker - Ra, Won-Sang; Whang, Ick-Ho; Shin, Hyo-Sang; Tsourdos, Antonios (Springer, 2017)
This paper proposes an efficient aimpoint tracking filter for high-range resolution FMCW radar seekers. A modified probabilistic data association scheme is devised to deal with closely located measurements generated by scatterers of an extended target and multipath clutter. In order to discriminate the aimpoint measurement from others, an approximate target range profile is used for calculating likelihoods of the validated measurements. Simulation results show the effectiveness and the superior performance of the proposed approach.
Keywords: Extended target tracking; probabilistic data association; target range profile; wideband FMCW seeker